Potential Role of Epigenetics and Redox Signaling in the Gut-Brain Communication and the Case of Autism Spectrum Disorder - Doenyas, Ceymi (SPRINGER/PLENUM PUBLISHERS, 2022)
The gut-brain axis refers to the bidirectional connection and communication between the gastrointestinal tract and the central nervous system. This paper explores two routes for this communication that have hitherto remained under-examined: epigenetics and redox signaling and their implications for autism spectrum disorder (ASD). The gut microbiota may induce epigenetic changes in the gut and potentially in the brain through their fermentation products. Instead of through other conceptualizations of them acting as neurotransmitters, gut microbial products may act as epigenetic agents, which are supported by the effects of gut bacterial-derived metabolites on gene regulation and expression. In addition to their epigenetic effects, gut bacterial-derived communicative agents can also influence host signaling by contributing to and even substituting host reactive oxygen species (ROS) production. These ROS can act as second messengers and exert oxidative activity on proteins to influence immune, inflammatory, and other signaling processes. ROS and epigenetic mechanisms may have interactive effects as well. ROS, in addition to their role in signaling pathways and cellular redox alterations, also influence redox-sensitive transcription factors, thereby having an effect on gene expression. Specifically, ROS are involved in the activation of transcription factors, chromatin remodeling, and histone/protein deacetylation. These two proposed mechanisms correspond with the recent findings related to ASD, where a cofactor that is shown to be lower in ASD has antioxidative properties, responds to epigenetic modulation, and increases via microbiota interventions. The current evidence reviewed here suggests the need to update models of the gut-brain communication to include these two mechanisms. Such a modeling can also contribute to understanding the unknowns of host metabolism and physiology in ASD and afford potential therapeutic avenues for this as well as other psychiatric and physiological conditions.
Keywords: Autism spectrum disorder; Epigenetics; Gut-brain communication; Redox signaling; Gut-brain axis; HYDROGEN-PEROXIDE; OXIDATIVE STRESS; TETRAHYDROBIOPTERIN; MICROBIOME; H2O2; Cell Biology; Neurosciences & Neurology